The Ant Genus Dorymyrmex Mayr (Hymenoptera: Formicidae: Dolichoderinae) in Colombia - Cuezzo, Fabiana del Carmen (2012)
The aim of this paper is to actualize the taxonomy of Dorymyrmex, by addressing problems at both the genus and the species levels. We also explore the taxonomy and distribution of Dorymyrmex in Colombia. We list, diagnose, and key nine species in the country, including three new species: Dorymyrmex amazonicus n. sp. Cuezzo & Guerrero, Dorymyrmex xerophylus n. sp. Cuezzo & Guerrero, and Dorymyrmex tuberosus n. sp. Cuezzo & Guerrero. We provide a detailed description of these new species based on the worker caste and, where possible, other castes. All localities where Dorymyrmex was collected or cited in the literature were mapped to provide a graphical view of its range.